α‐Synuclein RT‐QuIC assay in cerebrospinal fluid of patients with dementia with Lewy bodies - Matilde Bongianni; Anna Ladogana; Stefano Capaldi; Sigrid Klotz; Simone Baiardi; Annachiara Cagnin; Daniela Perra; Michele Fiorini; Anna Poleggi; Giuseppe Legname; Tatiana Cattaruzza; Francesco Janes; et al. (Annals of Clinical and Translational Neurology, 2019)
Abstract We applied RT‐QuIC assay to detect α‐synuclein aggregates in cerebrospinal fluid (CSF) of patients with suspected Creutzfeldt–Jakob disease who had a neuropathological diagnosis of dementia with Lewy bodies (DLB) (n = 7), other neurodegenerative diseases with α‐synuclein mixed pathology (n = 20), or without Lewy‐related pathology (n = 49). The test had a sensitivity of 92.9% and specificity of 95.9% in distinguishing α‐synucleinopathies from non‐α‐synucleinopathies. When performed in the CSF of patients with DLB (n = 36), RT‐QuIC was positive in 17/20 with probable DLB, 0/6 with possible DLB, and 0/10 with Alzheimer disease. These results indicate that RT‐QuIC for α‐synuclein is an accurate test for DLB diagnosis.